2006
DOI: 10.1370/afm.578
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Continuity of Care in Diabetes Mellitus: An Experience-Based Measure

Abstract: PURPOSE Continuity is an important attribute of health care, but appropriate measures are not currently available. We developed an experience-based measure of continuity of care in type 2 diabetes.METHODS A 19-item measure of experienced continuity of care for diabetes mellitus (ECC-DM) was developed from qualitative patient interview data with 4 continuity subdomains: longitudinal, fl exible, relational, and team and crossboundary continuity. The measure was implemented in a survey of 193 patients with type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Few researchers have attempted to do this. 3,22,23 However, others have argued that the importance of continuity stems partly from the sense of responsibility that it engenders in doctors. 18,24,25 This may be relevant even in situations when continuity is less important to individual patients, so it may be equally appropriate to assess whether doctors feel they are able to provide continuity.…”
Section: Whose Perspective?mentioning
confidence: 99%
“…Few researchers have attempted to do this. 3,22,23 However, others have argued that the importance of continuity stems partly from the sense of responsibility that it engenders in doctors. 18,24,25 This may be relevant even in situations when continuity is less important to individual patients, so it may be equally appropriate to assess whether doctors feel they are able to provide continuity.…”
Section: Whose Perspective?mentioning
confidence: 99%
“…Measures were needed of the patient's experience, especially of management continuity, and indeed, various measures were developed. Most, however, focus on a specifi c care context such as discharge from hospital, 5,6 or on single problems such as diabetes 7,8 heart disease, 9 or mental health. [10][11][12] Primary care requires a generic instrument, applicable to a broad range of health conditions (including multimorbidity) and patients in an ambulatory setting.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by a study conducted by Elrayah et al [18] in an urban town in Sudan in 2005 on economic burden of families of adult type 2 diabetes mellitus. That study reported that the economic burden of managing type 2 diabetes mellitus accounts for about 65% of family's expenditure on health [19]. Consequently, type 2 diabetic patients with poor glycaemic control may belong to families with low monthly income.…”
Section: Discussionmentioning
confidence: 99%